Liberal Feminism’s Representative of Visual Signs in Katy Perry’s Music Video “Dark Horse” - Aprilia Nur Diana; Murni Fidiyanti (UIBU, 2023)
Liberal feminism, a prominent faction within the feminist movement, advocates gender equality, individual freedom, and women's rights. Modern artistic works, notably music videos, often act as implicit visual manifestos for promoting these ideals. This study aimed to analyze visual signs representing liberal feminism in Katy Perry's